The Effect Of Sharia Capital Structure And Sharia Financing Structure On The Financial Performance Of Sharia Banking With Risk As An Intervening Variable - Zakiyyah Ilma Ahmad; Ahmad Zainul Abidin; Muhammad Khoirun Nasirin; Rakhmawan Habibi; Dimyati Dimyati (LPPM STIES BABUSSALAM, 2026)
The purpose of this study is to test and analyze the direct and indirect influence of sharia capital structure and sharia financing structure on financial performance through sharia banking risk. The type of research used is quantitative with a quantitative descriptive explanatory research analysis approach . The population in this study was 15 with a sample of 9 Islamic banks using the purposive sampling method . Data were collected using purposive sampling techniques through Islamic banking financial report data. The collected data was analyzed using Partial Least Square through the Smart-PLS application. The results of the study show: Sharia Capital Structure has a direct positive and significant influence on Financial Performance (1) Sharia Financing Structure has a direct negative and significant influence on Financial Performance, (2) Sharia Capital Structure has a direct negative and significant influence on Risk towards Sharia Banking, (3) Sharia Financing Structure has a direct negative and significant influence on Sharia Banking Risk, (4) Banking Risk towards Sharia has a direct negative and significant influence on Financial Performance, (5) Sharia Banking Risk has no influence and is not significant on the indirect relationship in mediating the relationship between Sharia Capital Structure towards Financial Performance and (6) Sharia Banking Risk has a positive and significant influence on the indirect relationship in mediating the relationship between Sharia Financing Structure towards Financial Performance.